A Revisiting Educational Paradigms of the Al-Khulafā’ Al-Rāsyidūn Period: Implications for Addressing Globalization-Era Educational Challenges - Tia Rahayu; Eva Dewi; Nur Aprilda Mardatillah (KURAS Institute, 2025)
This article explores the educational patterns prevalent during the period of al-Khulafā' al-Rāsyidūn, highlighting the values and methodologies of that time, which may serve as a framework for tackling modern educational challenges, particularly in the context of globalization. The research is prompted by the critical issue of diminishing spiritual and moral values amidst the rapid changes brought about by globalization. The goal of this study is to delineate the educational approaches of the al-Khulafā' al-Rāsyidūn and assess their relevance in addressing contemporary educational challenges. This research utilizes a qualitative methodology grounded in a literature review, drawing data from primary sources (including the Al-Qur'an, hadith, and classical Islamic texts) as well as secondary sources (such as academic journals, scholarly books, and recent studies related to the subject). The findings indicate that the educational framework during the al-Khulafā' al-Rāsyidūn period encompasses not only spiritual and moral growth but also practical and holistic elements. This includes strengthening faith, fostering moral character, and mastering knowledge, alongside enhancing the role of mosques as centers for learning. These insights contribute significantly to the development of a contemporary Islamic education model that is adaptive, distinctive, and pertinent to addressing the moral and identity crises faced by today’s Muslim generation.